Patterns in critical incidents: Understanding teacher retention through career decision making. (January 2022) - Hurst, Christopher; Brantlinger, Andrew
Abstract: Critical incidents are particular events that teachers report as important to their career decisions. This mixed methods study uses critical incidents to analyze how structural factors and teacher agency relate to mathematics teacher retention at the district level. The quantitative analysis of demographic, service history, and survey data identifies structural factors associated with retention. The subsequent, two-part qualitative analysis of teachers' self-reported critical incidents provides insights into the value these teachers place on student relationships, the job of teaching, and professional support. Given their power to explain teachers' retention outcomes, critical incidents merit serious attention by researchers and policymakers alike. Highlights: Teachers' perceptions of critical incidents affect their career decision making. Teacher retention is affected both by structural factors and by individual agency. A quantitative regression identifies salience of structural factors for retention. A qualitative analysis is used to describe teacher perceptions of critical incidents. A critical case analysis is used to describe surprising teacher retention decisions.